Pengaruh Motivasi Kerja, dan Lingkungan Kerja Terhadap Kinerja Karyawan CV. Har Gorden Palembang - Ira Mutiara Ramadhani; Maftuhah Nurrahmi; Lesi Agusria (As-Syirkah: Islamic Economic & Financial Journal, 2026)
This research aims to determine the influence of work motivation and work environment on CV employee performance. Har Gorden Palembang simultaneously and partially. The sample used was 62 respondents taken using Cluster Sampling. The analysis technique uses multiple linear regression, F and t hypothesis testing and the coefficient of determination. The results of research from multiple linear regression show that work motivation and work environment have a positive effect on CV employee performance. Har Gorden Palembang. The results of simultaneous hypothesis testing show that work motivation and work environment affect employee performance at CV. Har Gorden Palembang. Partially, it shows that work motivation significantly influences employee performance and the work environment significantly influences CV employee performance. Har Gorden Palembang. The results of the coefficient of determination show that the Work Motivation and Work Environment variables are able to contribute to the rise and fall of employee performance by 46.5%.